The Wiley Blackwell companion to patristics - Parry, Kenneth, 1945- (Hoboken : Wiley, 2015)
This comprehensive volume brings together a team of distinguished scholars to create a wide-ranging introduction to patristic authors and their contributions to not only theology and spirituality, but to philosophy, ecclesiology, linguistics, hagiography, liturgics, homiletics, iconology, and other fields.-Challenges accepted definitions of patristics and the patristic period - in particular questioning the Western framework in which the field has traditionally been constructed -Includes the work of authors who wrote in languages other than Latin and Greek, including those within the Coptic, Armenian, Syriac, and Arabic Christian traditions -Examines the reception history of prominent as well as lesser-known figures, debating the role of each, and exploring why many have undergone periods of revived interest -Offers synthetic accounts of a number of topics central to patristic studies, including scripture, scholasticism, and the Reformation -Demonstrates the continuing role of these writings in enriching and inspiring our understanding of Christianity.
The Gaps and Future DirectionsBibliography; Chapter 10 Augustine of Hippo; The Starting Point of Augustine's Reception: Augustine's Original Figure; Augustine's Reception in the Late Antique and Middle Ages; Reception of Augustine in the Modern Period; Augustine's Reception in China: The Case of Matteo Ricci's Mission; Augustine's Reception in Japan; Conclusion; Bibliography; Chapter 11 Cyril of Alexandria; Introduction; Christological Controversies; The Reception of Chalcedon; Texts and Translations; Middle Ages and Reformation; The Modern Period; Bibliography; Chapter 12 Shenoute of Atripe.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Fathers of the church; Fathers of the church (Title); Fathers of the church (Title); Fathers of the church; RELIGION -- Christian Church -- History; RELIGION -- Christianity -- History; Electronic books